Molecular analysis of homeostatic iron regulator, transmembrane protease serine-6, and BTB domain-containing protein-9 variants and iron parameters in blood donors - Fawzy, Manal S. (Biosci Rep, 2021)
Genetic variants associated with iron homeostasis have been identified, but their association with iron-related indices and variables among different ethnic populations remains controversial. We aimed to explore the genotype frequency and allelic distribution of three iron-metabolism related variants in homeostatic iron regulator gene (HFE; rs1800562 G/A), transmembrane protease, Serine-6 gene (TMPRSS6; rs855791 A/G), and BTB domain-containing protein-9 gene (BTBD9; rs9357271 C/T) among a sample of the Middle Eastern blood donors and to detect the association of these variants on blood indices, and serum hepcidin/ferritin levels. Real-Time TaqMan genotyping assay for the specified variants was applied for 197 unrelated blood donors. Complete blood picture and serum hepcidin/ferritin levels were assessed. All participants were carriers of rs1800562*G/G genotype for HFE. The frequency of A/A and A/G genotypes of TMPRSS6 rs855791 variant was 55% and 45%, and for C/C, C/T, and T/T of BTBD9 rs9357271, were 15%, 43%, and 42%, respectively. Minor allele frequencies of rs855791*G and rs9357271*C were 0.23 and 0.37. The GGC genotype combination (for HFE/TMPRSS6/BTBD9, respectively) was more frequent in male participants. Higher serum hepcidin and hepcidin/ferritin ratio were observed in TMPRSS6 (A/G) carriers. While subjects with BTBD9 C/T and TT genotypes had lower serum ferritin values and higher levels of hepcidin and hepcidin/ferritin ratio compared with C/C genotype. No significant associations were found with any other blood parameters. In conclusion, TMPRSS6 rs855791 (A/G) and BTBD9 rs9357271 (C/T) variants were prevalent in the present blood donor population and may influence the serum hepcidin and/or ferritin levels.